Testosterona e gonadotrofina coriônica humana estimulam a esteroidogênese em células da granulosa de folículo pré-ovulatório de égua? - Caldas-Bussiere, M.C.; Garcia, J.M. [UNESP]; Barbosa, J.C. [UNESP]; Rosa e Silva, A.A.M. (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2005)
Avaliou-se o papel da gonadotrofina coriônica humana (hCG) e da testosterona na produção de progesterona (P4) e 17beta -estradiol (E2) pelas células da granulosa cultivadas in vitro de folículo antral de égua. Os tratamentos usados foram: 1- controle (nenhum hormônio adicionado), 2- 1UI hCG (0,3mig/ml) e 3- 10UI hCG (3,0mig/ml). O tratamento com hCG foi realizado na presença ou não de testosterona (144ng/ml). O meio foi coletado e substituído com 0,25, 3, 6, 12, 24 e 144h de cultivo. As concentrações de P4 e E2 foram mensuradas por radioimunoensaio. Não se observou diferença entre os tratamentos 1 e 3 quanto à produção de P4 e E2; o tratamento 1 resultou em aumento da concentração de progesterona após 24h de cultura (P<0,01), mas somente em presença de testosterona. A concentração de estradiol aumentou em presença de testosterona, alcançando concentração máxima com 6h de cultura (P<0,01), e diminuiu gradativamente, até atingir a concentração observada com 0,25h de cultura. A adição de hCG não influenciou a síntese do estradiol. A testosterona desempenhou importante efeito estimulador na síntese/secreção doe E2 pelas células da granulosa e modulou a ação do hormônio luteinizante na diferenciação e luteinização das células da granulosa de folículo antral presumidamente pré-ovulatório de égua in vitro.

The role of the human chorionic gonadotropin (hCG) and testosterone was evaluated in the progesterone (P4) and estradiol-17beta (E2) production by granulosa cells of antral follicles from mare cultivated in vitro. The treatment (groups) with gonadotropin consisted of: 1- control (no added hormone); 2- 1 IU hCG (0.3mg/ml) and 3- 10 IU hCG (3.0mg/ml). The treatment with hCG was carried out in the presence or not of testosterone (144ng/ml). The culture medium was collected and replaced at 0.25, 3, 6, 12, 24 and 144h of culture. The concentrations of P4 and E2 were measured by radioimunoassay. Analyses of variance were used for P4 and E2, and mean of the factors were compared by the Tukey test at 5% of probability. No difference was observed between 1 and 2 groups. Treatment with 1 IU of hCG increased progesterone concentration after 24h of culture (P<0.01), only in the presence of testosterone. The concentration of estradiol increased in the presence of testosterone, reaching maximum concentration with 6h of culture (P<0.01), and reduced gradually until the observed concentration at 0.25h of culture. The addition of hCG had no effect in the synthesis of this steroid. The testosterone modulates the action of the luteinizing hormone in the differentiation and luteinization of the granulosa cells and plays important estimulator effect in the synthesis/secretion of E2 by granulosa cells in vitro of presumptive pre-ovulatory antral follicle in mare.
Do testosterone and human chorionic gonadotropin stimulate steroidogenesis in granulosa cells of preovulatory follicle in mare?
Keywords: égua hormônio luteinizante; testosterona; esteroidogênese; células da granulosa; mare; luteinizing hormone; testosterone; steroidogenesis; granulosa cell